Misplaced IUCD: a case report - Varun, Neha; Nigam, Aruna; Gupta, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
In a developing country like India where population census is crossing the limits, contraceptive methods are the necessary measures for the population control. Intrauterine Contraceptive devices (IUCDs) are the second most commonly used method of contraception after sterilization. Misplaced IUCDs usually present with the missing thread and remain asymptomatic in most of the cases. A case of a misplaced IUCD in the pouch of Douglas is reported which was managed laparoscopically.